SUPPLY CHAIN STRATEGY AND LABOR PARTNERSHIP AS A NATIONAL PRIORITY IN THE ECONOMIC DEVELOPMENT OF RUSSIA - Rossinskaya, Marina V.; Rokotyanskaya, Violetta V.; Bidova, Bela B.; Kanaeva, Alesya A.; Voloshina, Elena I. (International Journal of Supply Chain Management, 2020)
Abstract? Global competition has intensified geographic repositioning of supply chain activities with implications for the economic prosperity of specific regions and geographies affected by such shift. The article reflects the results of studies based on an interdisciplinary approach to the economic development by supply chain strategy and labor partnership. The work is aimed at clarifying the concept of supply chain management and labor partnership as an economic category. Therefore, this concept has been studied through the synthesis of jurisprudence, conflict management, sociology and political science, which allows to identify the economic and microeconomic substances of this phenomenon. The former is considered through the labor market trends and conditions, and quantified in derived parameters of supply chain and social-labor relations depending on it. The latter, as a specific type of management, is formed at the intersection of entrepreneurial, systemic management under limited conditions for self-management model implementation, typical for modern transition to the information, digital economy. Thus, a model of supply chain strategy and labor partnership has been developed as a microeconomic category, implying the impact characteristic of such management tools as investments in human capital, development of corporate culture, adequacy of compensation policies and supply chain responsibility tools, on social capital, considered as a synergistic amount of company?s human capital realized to the full. Additionally, a set of indicators developed in the course of research, and their dynamics can be used to monitor general trends in supply chain and labor partnership as an economic category. Our findings allow expanding the field of research and providing a scientific background for practical tools to improve economic relations.